Membangun Teologi Kesehatan Mental yang Berakar pada Kasih Karunia: Studi Konstruktif Pastoral di Kalangan Pemuda New Creation Church Manado - Christian Eko Wior (PT. Giat Konseling Nusantara, 2026)
The mental health crisis among youth has become a critical challenge for the contemporarychurch, including within the community of New Creation Church Manado. Many young peopleare struggling with emotional wounds stemming from broken homes, addiction to games andpornography, social pressure, depression, and guilt. This study aims to construct atheological framework of mental health rooted in grace, using a pastoral-constructive andintegrative approach that is contextually relevant. Through field observations and reflectivequalitative analysis, the study formulates five foundational pillars: (1) grace theology as thebasis of identity, (2) grace as a rejection of stigma and a path toward self-acceptance, (3)ecclesiology of grace as a healing community, (4) integration of theology and psychology insoul care, and (5) the healing journey from fallibility to fulfillment in Christ. The findingsshow that the local church can actively function as a healing community by embodying aculture of grace, embracing process, and cultivating hope beyond moralism. Thus, grace isnot merely a doctrine of salvation, but a holistic and sustainable path of soul restoration.